2017
DOI: 10.1039/c7cy01764b
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the highly tunable selectivity to linear α-olefins in Fischer–Tropsch synthesis over silica-supported Co and CoMn catalysts by carburization–reduction pretreatment

Abstract: An efficient strategy to tune the selectivity to α-olefins in FTS over Co-based catalysts has been developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
44
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 63 publications
8
44
0
3
Order By: Relevance
“…Figure c shows the H 2 ‐TPR profiles over Mn‐modified Fe 3 O 4 ‐ NaAc catalysts after calcination. It can be seen that a new reduction peak at around 315 °C appears with the addition of Mn; this is assigned to the reduction of MnO 2 to Mn 3 O 4 ,. The reduction peaks for Fe 3 O 4 ‐ NaAc at 410 and 624 °C are assigned to the reduction of Fe 3 O 4 to FeO, and FeO to α‐Fe, respectively, which distinctly shifts to lower temperature with the addition of Mn; this suggests that Mn could facilitate the reduction of Fe oxides.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure c shows the H 2 ‐TPR profiles over Mn‐modified Fe 3 O 4 ‐ NaAc catalysts after calcination. It can be seen that a new reduction peak at around 315 °C appears with the addition of Mn; this is assigned to the reduction of MnO 2 to Mn 3 O 4 ,. The reduction peaks for Fe 3 O 4 ‐ NaAc at 410 and 624 °C are assigned to the reduction of Fe 3 O 4 to FeO, and FeO to α‐Fe, respectively, which distinctly shifts to lower temperature with the addition of Mn; this suggests that Mn could facilitate the reduction of Fe oxides.…”
Section: Resultsmentioning
confidence: 99%
“…The decreased Fe 3 O 4 content seems to be transformed into χ‐Fe 5 C 2 . Indeed, the χ‐Fe 5 C 2 content is substantially higher for both Fe 3 O 4 ‐ NaAc and 0.09Mn/Fe 3 O 4 ‐ NaAc compared to that for Fe 3 O 4 ‐ pur and 0.09Mn/Fe 3 O 4 ‐ pur , which is in well accordance with XRD patterns (Figure b); this could be ascribed to the promoted carburization of metallic α‐Fe into χ‐Fe 5 C 2 due to the presence of Na for facilitating CO dissociation …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, carburization of the Co (111) phase using CO produces Co 2 C (111). The second reduction involving the Co 2 C (111) results in two phases: Co (101) and Co (002) …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, these authors observed that MnO x improved the dispersion of supported FeO x , facilitating its reduction and enhanching the carburization of FeO x . Interestingly, Xiaohao and co‐workers have recently investigated the addition of MnO x to a Co/SiO 2 FTS catalyst . These authors found that MnO x affects the formation of Co 2 C, a phase which has been recently shown to have a high selectivity towards lower olefins…”
Section: Resultsmentioning
confidence: 99%